2014
DOI: 10.1007/s00423-014-1258-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for recurrent goiter: complication rate and role of the thyroid-stimulating hormone-suppressive therapy after the first operation

Abstract: Our results clearly show that the interval between the two surgical interventions was significantly reduced in patients undergoing TSH-suppressive therapy with levothyroxine. The incidence of hypoparathyroidism dramatically increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…The mean interval between the initial and the reoperative procedure has been reported to be less than 20 years (14.9, 17.5, and 18.7 years in some previous series [ 2 , 5 , 10 ]). The mean intervals from the first operation to recurrence were more than 20 years (24 and 27 years in other series [ 11 , 12 ]). Recurrence in remnant thyroid has a slow progression rate as confirmed by 61.2% of our patients who had redo surgery after more than 20 years from primary surgery.…”
Section: Discussionmentioning
confidence: 80%
“…The mean interval between the initial and the reoperative procedure has been reported to be less than 20 years (14.9, 17.5, and 18.7 years in some previous series [ 2 , 5 , 10 ]). The mean intervals from the first operation to recurrence were more than 20 years (24 and 27 years in other series [ 11 , 12 ]). Recurrence in remnant thyroid has a slow progression rate as confirmed by 61.2% of our patients who had redo surgery after more than 20 years from primary surgery.…”
Section: Discussionmentioning
confidence: 80%
“…In the first randomized prospective study of 1,000 patients undergoing thyroid reoperation for recurrent goiter, Barczyński et al showed that the prevalence of transient RLN palsy was significantly lower among patients whose surgery utilized IONM (2.9% lower in high risk patients and 0.9% lower in low-risk patients) than among those whose operations involved only RLN visualization (39). Reoperations are undoubtedly more dangerous for the RLN than primary operations (11,12,14,15), hence the utilization of IONM should be always recommended to minimize the risk of nerve injury due to certain advantages the technique has over visual identification alone.…”
Section: Ionm In Recurrent Goitermentioning
confidence: 99%
“…Miccoli G et al 3 Prospective observational study N=214 -After the re-intervention there was temporary hypoparathyroidism in 37.7% of the patients, and definitive hypoparathyroidism occurred in 7.2%.…”
Section: Resultsmentioning
confidence: 99%
“…There are a number of known and frequent postoperative complications after a thyroidectomy such as hypocalcaemia (being the most frequent), the presence of re-bleeding leading to a hematoma with less or greater severity, recurrent laryngeal nerve paralysis. 1,3,5,6,7,9,10 According to Cauley et al 4 the complications recorded at 30 days out of a total of 40,025 patients undergoing total thyroidectomy were 7.74%. Preoperative factors that affected the complication rates for thyroidectomies in hospitalized patients included: age ≥70 years, non-Caucasian, dependent functional status, history of congestive heart failure, history of smoking, bleeding disorder (According to Quéralt et al 17 % vs. 13% of patients who performed hematoma were treated with anticoagulation) other complications were wound infection and preoperative sepsis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation